GIS-based model of wood procurement from stump to small sawmills in the Alpine region - a case study - Krč, Janez (Zbornik gozdarstva in lesarstva, 2009)
With wood logistics and forest operation modelling, we have connected a technologic chain of cutting, skidding and road wood transport operations. The goal of the paper is to present the possibilities of simulating forest operation activities including cost flow prediction. The case study regarding wood flow and forest operation cost modelling was conducted in four municipalities located in western Slovenia (bordering to Italy). Input data of forest inventory and basic forest data were used in order to predict the wood flow in the test area. We modelled the available cutting volumes with the capacities of local sinks - notably sawmills. Unbalanced hinterland areas of specific sinks that do not cover the local sink capacities were changed (reduced or enlarged) on account of the adjacent hinterland areas with surplus or shortage of wood volume. The hauling distances and wood volumes for covering the sawmillsć capacities of the adopted (balanced) hinterland areas were studied.
Keywords: les; logistika; modeli; oskrba; pridobivanje; žage